Impact of low-dose acetylsalicylic acid on pregnancy outcome in systemic lupus erythematosus: results from a multicentre study. Issue 1 (14th June 2022) - Tani, Chiara; Zucchi, Dina; Haase, Isabell; Gerosa, Maria; Larosa, Maddalena; Cavagna, Lorenzo; Bortoluzzi, Alessandra; Crisafulli, Francesca; Mucke, Johanna; Strigini, Francesca A L; Baglietto, Laura; Fornili, Marco; et al.
Abstract : Objective: It is still a matter of debate whether low-dose acetylsalicylic acid (LDASA) should be prescribed to all patients with SLE during pregnancy. This study aimed at investigating the impact of LDASA on pregnancy outcomes in patients with SLE without history of renal involvement and without antiphospholipid antibodies (aPL). Methods: This is a retrospective analysis of prospectively monitored pregnancies at seven rheumatology centres. Previous/current renal involvement and aPL positivity were the exclusion criteria. Adverse pregnancy outcome (APO) is the composite outcome of the study and included proteinuric pre-eclampsia, preterm delivery <37 weeks, small-for-gestational age infant, low birth weight <2500 g, intrauterine growth restriction and intrauterine fetal death after 12 weeks of gestation of a morphologically normal fetus. Results: 216 pregnancies in 187 patients were included; 82 pregnancies (38.0%) were exposed to LDASA treatment. No differences in terms of age at conception, disease duration, clinical manifestations, comorbidities and disease flare during pregnancy were observed between patients taking LDASA and those who did not take LDASA during pregnancy. APO was observed in 65 cases (30.1%), including 13 cases (6.1%) of pre-eclampsia. The incidence of all complications was similar in the two groups. However, it is interesting to note that pre-eclampsia had lower frequency in patients taking LDASA versus those not taking LDASA (2.4% vs 8.3%, p=0.14). Conclusions: In pregnant patients with SLE without renal involvement and were aPL-negative, there is a low risk of severe obstetric complications, such as early pre-eclampsia. LDASA treatment does not provide a statistically significant advantage over these complications. However, a careful individual risk–benefit balance is warranted.